Improving the Performance of Brimob Personnel: The Role of Reward, Training, and Professionalism - Ramli, Ramli; Lantara, Niniek F; Arif, Muhammad (Advances: Jurnal Ekonomi & Bisnis, 2023)
This study aims to analyze the effect of reward on the performance of Brimob personnel in South Sulawesi Regional Police through mediator factors, namely training and professionalism. The research method used was a survey with a sample of Brimob personnel at the South Sulawesi Regional Police. Data were collected through a questionnaire that had been tested for validity and reliability. Path analysis was used to test the research hypothesis. The results showed that rewards have a positive and significant effect on training, professionalism, and personnel performance. In addition, training and professionalism also have a positive and significant effect on personnel performance. These findings indicate the importance of implementing adequate rewards, good training, and a high level of professionalism in improving the performance of Brimob personnel. The implication of this study is the need for more serious attention to the reward system, the development of effective training programs, and increased professionalism in the Brimob organization. By understanding the influence of reward, training, and professionalism on personnel performance, the South Sulawesi Police can take strategic steps to improve the performance of their Brimob personnel.